Professional reading and the Medical Radiation Science Practitioner - Shanahan, M.; Herrington, Anthony; Herrington, J. (W.B. Saunders Co. Ltd., 2010)
Purpose. Updating professional knowledge is a central tenet of Continuing Professional Development (CPD) and professional reading is a common method health practitioners use to update their professional knowledge. This paper reports the level of professional reading by Medical Radiation Science (MRS) practitioners in Australia and examines organisational support for professional reading. Materials and Methods. Survey design was used to collect data from MRS practitioners. A questionnaire was sent to 1142 Australian practitioners, which allowed self-report data to be collected on the length of time practitioners engage in professional reading and the time workplaces allocate to practitioners for professional reading.Results. Of the 362 MRS practitioners who returned the survey, 93.9% engaged in professional reading on a weekly basis. In contrast, only 28.9% of respondents reported that their workplace allocates time for professional reading to practitioners. MRS practitioners employed in universities engaged in higher levels of reading than their colleagues employed in clinical workplaces (p < 0.01) and more university workplaces allocated time for professional reading to their employees than clinical workplaces (p < 0.01). There were no significant differences for clinical practitioners in level of reading across geographic, organisational and professional demographic factors. Significant differences in workplace allocation of time for professional reading in clinical workplaces were evident for health sector (p < 0.01); work environment (p < 0.01); geographic location (p < 0.01) and area of specialisation (p < 0.01).Conclusion. The vast majority of respondent MRS practitioners engage in professional reading to update their professional knowledge. This demonstrates an ongoing commitment at the individual practitioner level for updating professional knowledge. Updating professional knowledge is an organisational as well as an individual practitioner issue. Whilst the majority of organisations do not currently support MRS practitioners with time allocation for professional reading, there were organisations currently providing this form of support to their employees. Wider adoption of protected time for professional reading would provide much needed organisational support to practitioners and reduce the identified inequity that currently exists across the MRS profession.